Kinesiotherapy in the treatment of urinary incontinence in the elderly: Narrative review (Research, Society and Development, 2022)
Kinesiotherapy is a set of therapeutic exercises that help in the rehabilitation of different situations, strengthening and stretching the muscles, and can also serve to optimize the general state of health and prevent motor alterations. One of the diseases treated by kinesiotherapy is urinary incontinence, which is caused by the involuntary loss of urine through the urethra. The disorder is more frequent in females and can manifest itself in the fifth or sixth decade of life as well as in younger women. The present study aimed to describe Kinesiotherapy in the treatment of urinary incontinence in elderly women, through a narrative review. Searches were performed in the Scielo, BVS, Google academic database. The initial search resulted in 26 articles and, in the end, 20 articles were selected to compose this review. The present review found benefits of kinesiotherapy such as improving or curing urine loss, preventing urinary incontinence, re-educating and strengthening the pelvic muscles. It was found that Kinesiotherapy in the treatment of urinary incontinence in elderly women is important, as it works with exercises to strengthen the pelvic muscles, it reinforces urethral resistance and improves the supporting elements of the pelvic organs.